A Study On Saturation Flow Rates Of Through Vehicles At Signalised Intersections Based On Malaysian Road Conditions. [HE336.T7 L583 2004 f rb] [Microfiche 7668] - Leong, Lee Vien (2004)
Aliran tepu merupakan satu parameter yang penting dalam analisis kapasiti persimpangan berlampu isyarat.